2020
DOI: 10.1007/s42452-020-2162-0
|View full text |Cite
|
Sign up to set email alerts
|

LTA zeolite synthesis using natural materials and its evaluation by Green Star methodology

Abstract: The industrial costs of zeolite synthesis can be diminished by the substitution of traditional raw materials by natural sources. In this work, we obtained LTA zeolite from four natural materials, three different diatomites and expanded perlite, and characterize them by X-ray diffraction, X-ray fluorescence and scanning electron microscopy. It was possible to observe the formation of the zeolitic materials through the identification of the Bragg reflections and the cubic morphology characteristic of the alumino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…ZBG and ZCF illustrated the crystalline phases at 2θ of 7.2, 10.3, 12.6, 16.2, 21.8, 24, 26.2, 27.2, 30, 30.9, 31.1, 32.6, and 33.4 which represented the specific peaks of zeolite A characteristic. The results were correctly matched to the crystalline phases of STD and zeolite A standard pattern of JCPDS 39-222 [ 63 ] which confirmed that ZBG and ZCF were zeolite A [ 64 ].
Figure 3 XRD diffraction patterns of (a) ZBG, (b) ZCF, and (c) STD.
…”
Section: Resultssupporting
confidence: 53%
“…ZBG and ZCF illustrated the crystalline phases at 2θ of 7.2, 10.3, 12.6, 16.2, 21.8, 24, 26.2, 27.2, 30, 30.9, 31.1, 32.6, and 33.4 which represented the specific peaks of zeolite A characteristic. The results were correctly matched to the crystalline phases of STD and zeolite A standard pattern of JCPDS 39-222 [ 63 ] which confirmed that ZBG and ZCF were zeolite A [ 64 ].
Figure 3 XRD diffraction patterns of (a) ZBG, (b) ZCF, and (c) STD.
…”
Section: Resultssupporting
confidence: 53%
“…To reduce the production costs of synthetic zeolites, alternative sources of silicon and aluminum have been used. High-quality synthetic zeolites can be synthesized using a wide range of alternative sources, including natural aluminosilicates such as clays [8][9][10][11][12][13][14][15][16][17][18][19], natural zeolites [20,21], diatomite [22,23], and waste resources [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%